Effect of breed composition on sperm quality of boar - Valverde-Abarca, Anthony; Madrigal-Valverde, Mónica; Camacho-Calvo, Marlen; Zambrana-Jiménez, Adones; López, Leonardo (Agronomía Mesoamericana, 2018)
The assessment of the semen quality is an essential tool to improve the reproductive indexes in swine farms. The motility is the most important parameter that used in the sperm quality evaluation because it is associated with the energy of the spermatozoon. The aim of this research was to determine the influence of breed composition on reproductive variables of sperm quality, kinetics and semen motility in boars. During 2016, 240 ejaculates were collected from 63 boars with a mean age of 24.4±10.9 months. Six racial groups were identified: Duroc (D), Yorkshire (Y), Landrace (L), F1 Pietrain*Duroc (PD) and two genetic lines (LA and LB). The breeds with the highest ejaculate volume presented a higher total number of spermatozoa (P<0.05). The effect of the breed was significant (P<0.05) on sperm kinetics variables except for amplitude of lateral head displacement (ALH, μm). The Landrace breed presented the highest (P<0.05) percentage of static sperm (29.30±1.57). The most relevant differences (P<0.05) for total motility (MTOT) and progressive motility (MP), were presented between L and PD with values of 70.71±1.57; 77.48±1.09 and 51.80±1.97; 59.85±1.37% respectively. Adult boars (≥18 months) had higher volumes of ejaculate and total number of sperm than boars in the intermediate and young ages, however, for velocities (μm/s): curvilinear (VCL), straight line (VSL) and average path (VAP), adult boars only were different (P<0.05) of the boars in-between ages. Four sperm subpopulations (SP) were identified, SP1 (46.83%) characterized by a moderate speed, but of very progressive motility, SP2 (14.78%) with active movement, but not progressive, SP3 (8.45%) with low speeds and progressive path and SP4 (29.94%) with quick movement, but without progressivity.